1996
DOI: 10.1007/bf01411367
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid release from human cerebral cortex during simulated ischaemia in vitro

Abstract: The aim of the present study was to investigate the release of amino-acids in human cerebral cortex during membrane depolarization and simulated ischaemia (energy deprivation). Superfluous tissue from temporal Iobe resections for epilepsy was cut into 500 microns thick slices and incubated in vitro. Membrane depolarization with 50 mM K+ caused a release of glutamate, aspartate, GABA and glycine, but not glutamine or leucine. The release of glutamate and GABA was Ca(++)-dependent. Slices were exposed to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
4
7
0
Order By: Relevance
“…In con®rmation of earlier reports (e.g. Hegstad et al, 1996) ischaemia-induced glutamate release was inhibited dosedependently by GABA, maximal concentrations inhibiting 60 ± 70% of the ischaemia-induced glutamate e ux. The e ect of GABA was fully antagonized both by bicuculline, a competitive antagonist that acts at the agonist binding site on the GABA A receptor complex and by picrotoxin, a compound which occludes the open channel of the GABA A receptor complex.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In con®rmation of earlier reports (e.g. Hegstad et al, 1996) ischaemia-induced glutamate release was inhibited dosedependently by GABA, maximal concentrations inhibiting 60 ± 70% of the ischaemia-induced glutamate e ux. The e ect of GABA was fully antagonized both by bicuculline, a competitive antagonist that acts at the agonist binding site on the GABA A receptor complex and by picrotoxin, a compound which occludes the open channel of the GABA A receptor complex.…”
Section: Discussionsupporting
confidence: 90%
“…Benveniste et al, 1984;Baldwin et al 1994). However the magnitude of release observed here was similar to that reported in human cerebral cortex tissue in vitro (Hegstad et al, 1996). Hypoxia alone (without removal of glucose) also induced glutamate release (Baldwin et al, 1994), albeit of a somewhat lower magnitude than that produced by simulated ischaemia (current study).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Melani and colleagues used the brain microdialysis technique and demonstrated that after middle cerebral artery occlusion in the rat taurine was increased in the dialysate samples [34]. Interestingly, Heystad et al's study on the human cerebral cortex slice indicated that during membrane depolarization and simulated ischemia, the taurine release was increased [35]. Moreover, Castillo et al studied on 100 patients with infarction in the territory of the middle cerebral artery and reported that during the acute phase of cerebrovascular ischemia, the taurine concentration rise in the blood and cerebrospinal fluid [36].…”
Section: Discussionmentioning
confidence: 99%